A nurse–family partnership intervention to increase the self‐efficacy of family caregivers and reduce catheter‐associated urinary tract infection in catheterized patients1. Issue 6 (22nd April 2014) - Lee, Kwo‐Chen; Chao, Yann‐Fen C; Wang, Yueh‐Mien; Lin, Pi‐Chu
Abstract : The purpose of this study was to evaluate the effects of a nurse–family partnership model on the self‐efficacy of family caregivers (FCs) and the incidence of catheter‐associated urinary tract infection (CAUTI) among patients. A randomized controlled study was conducted. We recruited 61 patients and their FCs, who were randomly divided into an experimental group ( n = 30) and a control group ( n = 31). In the experimental group, the main caregivers comprised a nurse–family partnership, whereas the control participants received routine care. The findings were as follows: (i) the incidence of CAUTI was lower in the experimental group than in the control group (20% vs. 38.8%), but the difference was not statistically significant; and (ii) no significant difference emerged for reported Caregiver Self‐Efficacy Score between the two groups. The nursing team and FCs must become partners in cooperative caregiving to enhance the quality of patient care.